PENGARUH KOMPETENSI GURU DAN PROSES PEMBELAJARAN DALAM IMPLEMENTASI KURIKULUM 2013 TERHADAP HASIL BELAJAR KOGNITIF PADA MATA PELAJARAN PRINSIP–PRINSIP BISNIS KELAS XI PEMASARAN SMK NEGERI 1 KARANGANYAR TAHUN 2015/2016 - Lilis Lestari; Bambang Wasito Adi; Salman Alfarisy Totalia (Department of Economics Education, Universitas Sebelas Maret, 2018)
The aims of this research are to know: (1) the effect of the teacher’s competence in the implementation of 2013 Curriculum toward the students’ Cognitive learning achievement in the subject of Business Principles of XI Marketing class of SMK Negeri 1 Karanganyar, (2) the effect of the learning process in the implementation of 2013 Curriculum toward the students’ cognitive learning achievement in the subject of Business Principles of XI Marketing class of SMK Negeri 1 Karanganyar, (3) the effect of the teacher’s competence and learning process in the implementation of 2013 Curriculum toward the students’ cognitive learning achievement in the subject of Business Principles of XI Marketing class of SMK Negeri 1 Karanganyar. This is a casual associative research which used quantitative approach. The technique of sampling used in this research is convenience sampling/saturated sampling. The technique of collecting the data was done by using questionnaire. The technique of analyzing the data used was double regression, t-test and f-test.Based on the result of the research, it can be concluded that (1) there is an effect of the teacher’s competence in the implementation of 2013 Curriculum toward the student’s cognitive learning achievement in the subject of Business Principles of XI Marketing class. It can be shown by the score of tstatistic > ttest; 9,552 > 1,667. (2) There is an effect of the learning process in the implementation of 2013 Curriculum toward the student’s learning achievement in the subject of Business Principles of XI Marketing class. It can be shown by the score of tstatistic > ttable; 2,036 > 1,667. (3) There is an effect of the teacher’s competence and learning process in the implementation of 2013 Curriculum toward the student’s learning achievement in the subject of Business Principles of XI Marketing class. It can be shown by the score of tstatistic > ttable; 51,726 > 3,128.